Study of UiO-66 and UiO-66 Modulated with Acetic Acid as the Adsorbent for Eriochrome Black T Dye - Pambudi, M. Anugrah Rizky; Prayogo, Nanda; Nadjib, Muhammad; Ediati, Ratna (Indonesian Journal of Chemical Research, 2021)
UiO-66, as one of the metal-organic framework (MOF) compounds, has been used to treat some anionic and cationic dye waste. In order to determine the adsorption selectivity decisively, the synthesis of UiO-66 and UiO-66 modulated with acetic acid had been carried out, along with their adsorption tests for Eriochrome Black T (EBT) dye solution. The synthesis was performed by utilizing a solvothermal method with the reaction mixtures of zirconium (IV) chloride (ZrCl4) and terephthalic acid (H2BDC) as a ligand heated at 120 oC for 24 hours. Both UiO-66 (without acetic acid) and acetic acid modulated UiO-66 were obtained as a white powder. Acetic acid as a modulator was added and being investigated for the adsorption capability compared to the normal UiO-66. This study showed that normal UiO-66 exhibited better adsorption than acetic acid modulated UiO-66 with a mmol ratio of acetic acid:ligand varied from 50:1, 100:1, and 150:1. Acetic acid modulated UiO-66 with a mmol ratio of 50 exhibited the best crystallinity as observed by using x-ray diffraction. It can be concluded that the adsorption of EBT using normal and acetic acid modulated UiO-66 obeyed the pseudo-second-order reaction rate law as well as the Langmuir adsorption isotherm pattern.